PRELIMINARY ANALYSIS OF GENOTYPIC AND PHENOTYPIC CORRELATION OF TRAITS IN DROUGHT TOLERANT POTATO UNDER MOISTURE DEFICIT AREAS OF NORTH-WESTERN ETHIOPIA - Mebratie, Berhan Gashaw; Mohammed, Wassu (Potato Journal, 2021)
ABSTRACT : This study was conducted at Adet Agricultural Research Center, Simada (NW-Ethiopia) a site for drought experiments in the 2016 main rain season. It aimed at estimating associations among yields and yield contributing traits of 105 potato genotypes comprised five standard checks. Augmented design was used and data were collected for 20 traits. Marketable and total tuber yield ranged from 10.8 to 39.0 and 13.9 to 41.8 t ha-1, respectively. Total tuber yield was significantly positively correlated with leaf area, tuber number per plant, tuber yield per plant, marketable tuber yield, bulking rate, large size tubers percentage and average tuber weight. In tuber quality parameters (tuber dry matter, specific gravity and total starch content) there were highly significant and positive genotypic correlation among them and also they were positively correlated in phenotype. Thus, potato tuber yield enhancement may be possible through indirect selection of positively correlated traits simultaneously. Â